Oligella ureolytica conjunctivitis in a female patient - Giuseppe Ivan Potente; Francesca Fabiola Bianco; Raffaella Aiello (Microbiologia Medica, 2016)
Oligella ureolytica, an aerobic gram-negative found as a commensal microorganism in human urinary tracts, is an emerging bacteria which is rarely implicated as human pathogen. In the past referred to as CDC Group IVe, this bacterium is not commonly encountered as a source of infection and is difficult to isolate by means of conventional laboratory procedures. We present here the case of a 55-year-old female patient suffering from bilateral conjunctivitis. An Oligella ureolytica infection was identify in an eye swab sample. The pathogen was isolated in pure culture (48/72 h) and an antibiogram was determined by Kirby-Bauer disc diffusion method (manual test).